Highly wear-resistant self-reinforced wood-stone material and preparation method thereof
By adding carbon fiber/polyether etherketone/polyethyleneimine composites to wood and stone materials and strictly controlling the order of addition of each component, the problems of poor mechanical properties and insufficient wear resistance of wood and stone materials have been solved, and significant It has improved wear resistance and mechanical properties, suitable for industrial production.
Patent Information
- Application Number
- CN202410727208.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The existing wood and stone materials have poor mechanical properties and are not resistant to wear and friction during long-term use.
High wear-resistant self-reinforced wood and stone materials are prepared by adding carbon fiber/polyether etherketone/polyethyleneimine composites to the wood and stone materials, and strictly controlling the order and timing of each component are strictly controlled.
It significantly improves the wear resistance and mechanical properties of wood and stone materials. The combination of carbon fiber and polyether ether ketone improves compatibility and connection strength, making it suitable for industrial production.
Smart Images

Figure BDA0004879004100000101 
Figure BDA0004879004100000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wood-stone materials, and in particular to a highly wear-resistant self-reinforced wood-stone material and a preparation method thereof. Background Art
[0002] Wood-stone material is a composite material made of stone powder (the main component is usually calcium carbonate) and wood fiber / wood powder as the main materials, supplemented by polymer materials such as polyvinyl chloride and processing aids. Stone powder accounts for the highest proportion in the raw material system. The prepared wood-stone material has the advantages of natural environmental protection, no formaldehyde addition, good moisture resistance, etc.
[0003] Because wood and stone materials have the above-mentioned excellent properties, they are gradually used in the home furnishing field, such as being made into door panels or door frames. The service life of household door panels / door frames is usually measured in years. During long-term use, the surface of the door panels / door frames needs to have excellent wear resistance, and they also need to have excellent mechanical properties such as impact resistance to meet the wear and tear in daily life and resist friction in daily life.
[0004] The prior art usually adds reinforcing / toughening agents to the wood-stone material system to improve the impact resistance of the wood-stone material, but the improvement of the wear resistance is limited. The present invention provides a highly wear-resistant self-reinforced wood-stone material and a preparation method thereof, which significantly improves the mechanical properties and wear resistance of the wood-stone material. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a highly wear-resistant self-reinforced wood-stone material and a preparation method thereof, which solves the problem that the existing wood-stone materials have poor mechanical properties and are not resistant to wear and friction during long-term use.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] Highly wear-resistant self-reinforced wood-stone material, 100-120 parts of stone powder, 50-80 parts of wood powder, 15-30 parts of polyvinyl chloride, 10-20 parts of aluminum hydroxide, 10-15 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2-2.5 parts of foaming agent, 10-15 parts of foaming regulator, 5-7 parts of stabilizer, 0.6-1.5 parts of stearic acid and 0.4-0.6 parts of oxidized polyethylene wax.
[0010] Preferably, the preparation method of the carbon fiber / polyetheretherketone / polyethyleneimine composite is:
[0011] 1) Weigh carbon fiber, polyetheretherketone, and polyethyleneimine for later use;
[0012] 2) Add polyetheretherketone and polyethyleneimine into a 330-350°C water bath and heat for 15-25 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add plasticizer and defoamer and stir them thoroughly.
[0013] 3) adding carbon fiber to the system of step 2) and further stirring evenly;
[0014] 4) Add the curing agent to a 60-80°C water bath and heat for 15-25 minutes. When it is molten and flowing, add it to the system of step 3), accelerate the stirring until the composite material is evenly mixed, perform molding, and place it at room temperature to gradually cool and solidify.
[0015] Preferably, the mass ratio of the carbon fiber, the polyetheretherketone and the polyethyleneimine is 1:(2.5-3.5):(0.2-0.4).
[0016] Preferably, the added amounts of the plasticizer and the defoamer are 0.5-0.8% of the total added amount of the polyetheretherketone and the polyethyleneimine, respectively.
[0017] Preferably, the curing agent is polyamide; the plasticizer is dibutyl phthalate; and the defoaming agent is dimethyl silicone oil.
[0018] Preferably, the carbon fiber is pre-treated before being put into preparation, and the pre-treatment method is:
[0019] 1) Place the carbon fiber in an extractor for reflux treatment to remove surface rubber and impurities;
[0020] 2) Adding polydopamine powder and carbon nanotube powder to acetone, stirring the mixture continuously for 1 to 2 hours, and ultrasonically dispersing the mixture for 0.5 to 1 hour to make it uniformly dispersed;
[0021] 3) Soak the carbon fiber in the suspension prepared in step 2) for 40 to 60 seconds, take it out, and dry it at 85 to 95° C. for 2 to 2.5 hours. The pretreatment is completed.
[0022] Preferably, the added amount of the polydopamine powder is 1-1.5% of the mass of the acetone, and the added amount of the carbon nanotube powder is 0.4-0.8% of the mass of the acetone.
[0023] Preferably, the foaming agent is sodium lauryl sulfate or sodium polyoxyethylene fatty alcohol ether sulfate; the foaming regulator is any one of ZB-530, K-400, and JINHASS foaming regulators; and the stabilizer is an organic tin stabilizer or a calcium zinc stabilizer.
[0024] The preparation method of the highly wear-resistant self-reinforced wood-stone material specifically comprises the following steps:
[0025] S1. Raw material preparation: weigh 100-120 parts of stone powder, 50-80 parts of wood powder, 15-30 parts of polyvinyl chloride, 10-20 parts of aluminum hydroxide, 10-15 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2-2.5 parts of foaming agent, 10-15 parts of foaming regulator, 5-7 parts of stabilizer, 0.6-1.5 parts of stearic acid and 0.4-0.6 parts of oxidized polyethylene wax;
[0026] S2. Mixing and batching: The stone powder, wood powder, polyvinyl chloride, and aluminum hydroxide are first mixed evenly, and then the foaming agent and the foaming regulator are added and mixed again. After mixing evenly, the carbon fiber / polyetheretherketone / polyethyleneimine composite is added;
[0027] S3 extrusion: the mixture is placed in an extruder, until the mixture is melted and blended uniformly, a stabilizer, stearic acid and polyethylene oxide are added, and blended uniformly, and the blend is extruded;
[0028] S4. Molding and cooling: The extruded mixture is cooled and vacuum-shaped through a mold;
[0029] S5. Cutting and trimming: Cut and trim the formed products according to production requirements;
[0030] S6. Inspection: Carry out quality inspection on the products, check their size, appearance and performance, and produce and put them into storage after they pass the inspection.
[0031] The highly wear-resistant self-reinforced wood-stone material or the wood-stone material prepared using the method for preparing the highly wear-resistant self-reinforced wood-stone material is applied to the field of door panels or door frames.
[0032] (III) Beneficial effects
[0033] The present invention provides a highly wear-resistant self-reinforced wood-stone material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention adds a carbon fiber / polyetheretherketone / polyethyleneimine composite to the wood-stone material system. The prepared wood-stone material has excellent wear resistance and mechanical properties. The carbon fiber has the characteristics of high temperature resistance, friction resistance, thermal conductivity and corrosion resistance. The polyetheretherketone has excellent characteristics such as high strength, high stability and easy processing. After being combined with the carbon fiber, it can also improve the poor compatibility of the carbon fiber in the system. The addition of a small amount of polyethyleneimine can further enhance the connection strength between the carbon fiber and the polyetheretherketone on the one hand, and further improve the compatibility of the composite in the system on the other hand;
[0035] 2. When preparing the wood-stone material, the present invention strictly controls the order and timing of adding each component, so that the prepared wood-stone material has excellent wear resistance and mechanical properties;
[0036] 3. The preparation method of the present invention is simple, the process is easy to operate, and is suitable for industrial production. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The embodiments of the present application solve the problem that the existing wood and stone materials have poor mechanical properties and are not resistant to wear and friction during long-term use by providing a highly wear-resistant self-reinforced wood and stone material and a preparation method thereof.
[0039] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0040] All raw materials used in the present invention are purchased from cooperative manufacturers.
[0041] Embodiment 1:
[0042] The highly wear-resistant self-reinforced wood-stone material comprises the following components in parts by weight: 100 parts of stone powder, 50 parts of wood powder, 15 parts of polyvinyl chloride, 10 parts of aluminum hydroxide, 10 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2 parts of sodium lauryl sulfate, 10 parts of ZB-530 foaming regulator, 5 parts of organic tin stabilizer, 0.6 parts of stearic acid and 0.4 parts of oxidized polyethylene wax.
[0043] The preparation method of the highly wear-resistant self-reinforced wood-stone material specifically comprises the following preparation steps:
[0044] S1. Pre-treatment of carbon fiber:
[0045] S1.1. The carbon fiber is placed in an extractor for reflux treatment to remove surface rubber and impurities;
[0046] S1.2. 1 wt% polydopamine powder and 0.4 wt% carbon nanotube powder were added to acetone, the mixture was stirred continuously for 1 h, and ultrasonically dispersed for 0.5 h to make it uniformly dispersed;
[0047] S1.3. Soak the carbon fiber in the suspension prepared in step S1.2 for 40 seconds, take it out, and dry it at 85°C for 2 hours. The pretreatment is completed.
[0048] S2. Preparation of carbon fiber / polyetheretherketone / polyethyleneimine composite:
[0049] S2.1. Weigh carbon fiber, polyetheretherketone, and polyethyleneimine in a mass ratio of 1:2.5:0.2 for later use;
[0050] S2.2. Add polyetheretherketone and polyethyleneimine to a 330°C water bath and heat for 15 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add 0.5% of the total weight of polyetheretherketone and polyethyleneimine, respectively, to dibutyl phthalate and dimethyl silicone oil, and stir well;
[0051] S2.3. Add carbon fiber to the system of step S2.2 and further stir evenly;
[0052] S2.4. Add polyamide to a 60°C water bath and heat for 15 minutes. When it is molten and flowing, add it to the system of step 3), accelerate stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify.
[0053] S3. Preparation of highly wear-resistant self-reinforced wood-stone materials:
[0054] S3.1. Raw material preparation: weigh the above raw materials by weight;
[0055] S3.2. Mixing and batching: first mix the stone powder, wood powder, polyvinyl chloride and aluminum hydroxide evenly, then add sodium lauryl sulfate and ZB-530 foaming regulator and mix again, after mixing evenly, add the carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0056] S3.3 Extrusion: The mixture is placed in an extruder, and after the mixture is melted and blended evenly, an organic tin stabilizer, stearic acid and polyethylene oxide are added, and blended evenly, and the blend is extruded and formed;
[0057] S3.4. Molding and cooling: The extruded mixture is cooled and vacuum-shaped through a mold;
[0058] S3.5. Cutting and trimming: Cut and trim the formed products according to production requirements;
[0059] S3.6. Inspection: Carry out quality inspection on the products, check their size, appearance and performance, and produce and put them into storage after they pass the inspection.
[0060] Embodiment 2:
[0061] The highly wear-resistant self-reinforced wood-stone material comprises the following components in parts by weight: 110 parts of stone powder, 65 parts of wood powder, 22 parts of polyvinyl chloride, 15 parts of aluminum hydroxide, 12.5 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2.25 parts of fatty alcohol polyoxyethylene ether sodium sulfate, 12.5 parts of K-400 foaming regulator, 6 parts of calcium zinc stabilizer, 1.1 parts of stearic acid and 0.5 parts of oxidized polyethylene wax.
[0062] The preparation method of the highly wear-resistant self-reinforced wood-stone material specifically comprises the following preparation steps:
[0063] S1. Pre-treatment of carbon fiber:
[0064] S1.1. The carbon fiber is placed in an extractor for reflux treatment to remove surface rubber and impurities;
[0065] S1.2. 1.25 wt% polydopamine and 0.6 wt% carbon nanotube powder were added to acetone, and the mixture was stirred continuously for 1.5 h and ultrasonically dispersed for 0.75 h to make it uniformly dispersed;
[0066] S1.3. Soak the carbon fiber in the suspension prepared in step S1.2 for 50 seconds, take it out, and dry it at 90°C for 2.25 hours. The pretreatment is completed.
[0067] S2. Preparation of carbon fiber / polyetheretherketone / polyethyleneimine composite:
[0068] S2.1. Weigh carbon fiber, polyetheretherketone, and polyethyleneimine in a mass ratio of 1:3:0.3 for later use;
[0069] S2.2. Add polyetheretherketone and polyethyleneimine to a 340°C water bath and heat for 20 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add dibutyl phthalate and dimethyl silicone oil accounting for 0.65% of the total weight of polyetheretherketone and polyethyleneimine, respectively, and stir well;
[0070] S2.3. Add carbon fiber to the system of step S2.2 and further stir evenly;
[0071] S2.4. Add the polyamide to a 70°C water bath and heat for 20 minutes. When it is molten and flowing, add it to the system of step 3), accelerate the stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify.
[0072] S3. Preparation of highly wear-resistant self-reinforced wood-stone materials:
[0073] S3.1. Raw material preparation: weigh the above raw materials by weight;
[0074] S3.2. Mixing and batching: first mix the stone powder, wood powder, polyvinyl chloride and aluminum hydroxide evenly, then add the sodium sulfate of fatty alcohol polyoxyethylene ether and K-400 foaming regulator and mix again, after mixing evenly, add the carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0075] S3.3 Extrusion: The mixture is placed in an extruder, and after the mixture is melted and blended evenly, a calcium zinc stabilizer, stearic acid and oxidized polyethylene are added, and blended evenly, and the blend is extruded and formed;
[0076] S3.4. Molding and cooling: The extruded mixture is cooled and vacuum-shaped through a mold;
[0077] S3.5. Cutting and trimming: Cut and trim the formed products according to production requirements;
[0078] S3.6. Inspection: Carry out quality inspection on the products, check their size, appearance and performance, and produce and put them into storage after they pass the inspection.
[0079] Example 3
[0080] The highly wear-resistant self-reinforced wood-stone material comprises the following components in parts by weight: 120 parts of stone powder, 80 parts of wood powder, 30 parts of polyvinyl chloride, 20 parts of aluminum hydroxide, 15 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2.5 parts of sodium lauryl sulfate, 15 parts of JINHASS foaming regulator, 7 parts of organic tin stabilizer, 1.5 parts of stearic acid and 0.6 parts of oxidized polyethylene wax.
[0081] The preparation method of the highly wear-resistant self-reinforced wood-stone material specifically comprises the following preparation steps:
[0082] S1. Pre-treatment of carbon fiber:
[0083] S1.1. The carbon fiber is placed in an extractor for reflux treatment to remove surface rubber and impurities;
[0084] S1.2. 1.5 wt% polydopamine powder and 0.8 wt% carbon nanotube powder were added to acetone, and the mixture was stirred continuously for 2 h and ultrasonically dispersed for 1 h to make it uniformly dispersed;
[0085] S1.3. Soak the carbon fiber in the suspension prepared in step S1.2 for 60 seconds, take it out, and dry it at 95°C for 2.5 hours. The pretreatment is completed.
[0086] S2. Preparation of carbon fiber / polyetheretherketone / polyethyleneimine composite:
[0087] S2.1. Weigh carbon fiber, polyetheretherketone, and polyethyleneimine in a mass ratio of 1:3.5:0.4 for later use;
[0088] S2.2. Add polyetheretherketone and polyethyleneimine to a 350°C water bath and heat for 25 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add dibutyl phthalate and dimethyl silicone oil accounting for 0.8% of the total weight of polyetheretherketone and polyethyleneimine, respectively, and stir well;
[0089] S2.3. Add carbon fiber to the system of step S2.2 and further stir evenly;
[0090] S2.4. Add polyamide to a water bath at 80°C and heat for 25 minutes. When it is molten and flowing, add it to the system of step S2.3, accelerate the stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify.
[0091] S3. Preparation of highly wear-resistant self-reinforced wood-stone materials:
[0092] S3.1. Raw material preparation: weigh the above raw materials by weight;
[0093] S3.2. Mixing and batching: first mix the stone powder, wood powder, polyvinyl chloride and aluminum hydroxide evenly, then add sodium lauryl sulfate and JINHASS foaming regulator and mix again, after mixing evenly, add the carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0094] S3.3 Extrusion: The mixture is placed in an extruder, and after the mixture is melted and blended evenly, an organic tin stabilizer, stearic acid and polyethylene oxide are added, and blended evenly, and the blend is extruded and formed;
[0095] S3.4. Molding and cooling: The extruded mixture is cooled and vacuum-shaped through a mold;
[0096] S3.5. Cutting and trimming: Cut and trim the formed products according to production requirements;
[0097] S3.6. Inspection: Carry out quality inspection on the products, check their size, appearance and performance, and produce and put them into storage after they pass the inspection.
[0098] Embodiment 4 is different from Embodiment 2 in that:
[0099] No pre-treatment of the carbon fiber is performed.
[0100] Comparative Example 1 is different from Example 2 in that:
[0101] The carbon fiber / polyetheretherketone / polyethyleneimine composite is not added to the wood-stone material system.
[0102] Comparative Example 2 is different from Example 2 in that:
[0103] Directly add pre-treated carbon fiber to the wood-stone material system instead of carbon fiber / polyetheretherketone / polyethyleneimine composite.
[0104] Comparative Example 3 is different from Example 2 in that:
[0105] The carbon fiber / polyetheretherketone composite is directly added to the wood-stone material system, rather than the carbon fiber / polyetheretherketone / polyethyleneimine composite.
[0106] The preparation method of the carbon fiber / polyetheretherketone composite is as follows:
[0107] Weigh carbon fiber and polyetheretherketone in a mass ratio of 1:3.9 for later use;
[0108] S2.2. Add polyetheretherketone to a 330°C water bath and heat for 25 minutes. When the polyetheretherketone melts and flows, add 0.8% of the total weight of polyetheretherketone to dibutyl phthalate and dimethyl silicone oil, respectively, and stir well;
[0109] S2.3. Add carbon fiber to the system of step S2.2 and further stir evenly;
[0110] S2.4. Add polyamide to a water bath at 80°C and heat for 25 minutes. When it is molten and flowing, add it to the system of step S2.3, accelerate the stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify.
[0111] Comparative Example 4 is different from Example 2 in that:
[0112] A carbon fiber / polyethylene / polyethyleneimine composite is added to the wood-stone material system to replace the carbon fiber / polyetheretherketone / polyethyleneimine composite.
[0113] The preparation method of the carbon fiber / polyethylene / polyethyleneimine composite is as follows:
[0114] S2.1. Weigh carbon fiber, polyethylene, and polyethyleneimine in a mass ratio of 1:3.5:0.4 for later use;
[0115] S2.2. Add polyetheretherketone and polyethyleneimine to a 100°C water bath and heat for 25 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add dibutyl phthalate and dimethyl silicone oil accounting for 0.8% of the total weight of polyetheretherketone and polyethyleneimine, respectively, and stir well;
[0116] S2.3. Add carbon fiber to the system of step S2.2 and further stir evenly;
[0117] S2.4. Add polyamide to a water bath at 80°C and heat for 25 minutes. When it is molten and flowing, add it to the system of step S2.3, accelerate the stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify.
[0118] Comparative Example 5 is different from Example 2 in that:
[0119] When pre-treating the carbon fiber, 0.8 wt % of polydopamine powder and 1 wt % of carbon nanotube powder were added to acetone.
[0120] Comparative Example 6 is different from Example 2 in that:
[0121] During the pretreatment of carbon fiber, 1.8 wt % of polydopamine powder and 0.2 wt % of carbon nanotube powder were added to acetone.
[0122] Comparative Example 7 is different from Example 2 in that:
[0123] When preparing the carbon fiber / polyetheretherketone / polyethyleneimine composite, carbon fiber, polyetheretherketone and polyethyleneimine in a mass ratio of 1:2:0.3 are weighed for later use.
[0124] Comparative Example 8 is different from Example 2 in that:
[0125] When preparing the carbon fiber / polyetheretherketone / polyethyleneimine composite, carbon fiber, polyetheretherketone and polyethyleneimine in a mass ratio of 1:3:0.5 are weighed for later use.
[0126] Comparative Example 9 is different from Example 2 in that:
[0127] When preparing the carbon fiber / polyetheretherketone / polyethyleneimine composite, carbon fiber, polyetheretherketone and polyethyleneimine in a mass ratio of 1:2:0.1 are weighed and set aside.
[0128] Comparative Example 10 is different from Example 2 in that:
[0129] When preparing the carbon fiber / polyetheretherketone / polyethyleneimine composite, carbon fiber, polyetheretherketone and polyethyleneimine in a mass ratio of 1:4:0.5 are weighed for later use.
[0130] Comparative Example 11 is different from Example 2 in that:
[0131] When preparing highly wear-resistant self-reinforced wood-stone materials,
[0132] S3.2. Mixing and batching: First, mix the stone powder, wood powder, polyvinyl chloride and aluminum hydroxide evenly, then add sodium lauryl sulfate, JINHASS foaming regulator, organic tin stabilizer, stearic acid and polyethylene oxide and mix them again. After mixing evenly, add the carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0133] S3.3. Extrusion: Place the mixture into an extruder, and after the mixture is melted and blended evenly, extrude the mixture into shape.
[0134] Comparative Example 12 is different from Example 2 in that:
[0135] When preparing highly wear-resistant self-reinforced wood-stone materials,
[0136] S3.2. Mixing and batching: First, mix the stone powder, wood powder, polyvinyl chloride, aluminum hydroxide, carbon fiber / polyetheretherketone / polyethyleneimine compound evenly, then add sodium lauryl sulfate, JINHASS foaming regulator, organic tin stabilizer, stearic acid and oxidized polyethylene and mix evenly;
[0137] S3.3. Extrusion: Place the mixture into an extruder, and after the mixture is melted and blended evenly, extrude the mixture into shape.
[0138] Performance Testing
[0139] The wood and stone materials prepared in Examples 1-4 and Comparative Examples 1-12 were sampled, and the following performance tests were performed on the samples.
[0140] 1. Wear resistance test
[0141] The samples were subjected to surface inspection and wear test, and the wear rate was used to characterize the wear resistance of the samples. The specific test results are recorded in Table 1 below.
[0142] Table 1- Samples’ apparent performance and wear resistance test data
[0143]
[0144]
[0145] 2. Mechanical properties testing
[0146] The samples were subjected to surface inspection and wear test, and the wear rate was used to characterize the wear resistance of the samples. The specific test results are recorded in Table 1 below.
[0147] Table 2- Mechanical properties test data of samples
[0148] sample Tensile strength / (Mpa) <![CDATA[Impact strength / (kJ / m 2 )]]> Example 1 42.6 17.8 Example 2 44.1 18.4 Example 3 43.7 17.1 Example 4 39.5 15.0 Comparative Example 1 20.6 8.3 Comparative Example 2 29.4 11.5 Comparative Example 3 33.1 14.4 Comparative Example 4 36.9 14.9 Comparative Example 5 40.5 15.8 Comparative Example 6 41.7 15.1 Comparative Example 7 41.2 15.4 Comparative Example 8 40.3 16.0 Comparative Example 9 39.1 14.9 Comparative Example 10 40.3 15.0 Comparative Example 11 38.9 15.9 Comparative Example 12 39.5 16.4
[0149] From the data in Table 1 and Table 2, we can see that:
[0150] 1. It can be seen from Examples 1-4 that pre-treating the carbon fiber before using it is beneficial to improve the connection strength between the carbon fiber and polyetheretherketone and polyethyleneimine, so that the prepared carbon fiber / polyetheretherketone / polyethyleneimine has excellent mechanical properties. Applying it to the system of wood and stone materials can significantly improve the wear resistance and mechanical properties of the wood and stone materials;
[0151] 2. It can be seen from Examples 1-3 and Comparative Examples 1-4 that the three components of the carbon fiber / polyetheretherketone / polyethyleneimine composite have a synergistic effect. Replacing polyetheretherketone with polyethylene or using only carbon fiber composite polyetheretherketone or only using carbon fiber composite polyethyleneimine cannot achieve the technical effect of using the carbon fiber / polyetheretherketone / polyethyleneimine composite. Therefore, the carbon fiber / polyetheretherketone / polyethyleneimine composite of the technical solution of the present application is added to the wood-stone material system to significantly improve the wear resistance and mechanical properties of the wood-stone material.
[0152] 3. It can be seen from Examples 1-3 and Comparative Examples 5-6 that the addition amount of polydopamine powder and carbon nanotube powder will have a certain influence on the wear resistance and mechanical properties of wood and stone materials. Too much or too little addition or an inappropriate addition ratio of the two components will lead to a decrease in the mechanical properties and wear resistance of the wood and stone materials.
[0153] 4. It can be seen from Examples 1-3 and Comparative Examples 7-10 that the addition ratio of the three components of carbon fiber, polyetheretherketone and polyethyleneimine will affect the mechanical properties and wear resistance of the prepared carbon fiber / polyetheretherketone / polyethyleneimine composite. This is because, when designing the technical solution of the present invention, polyethyleneimine is added as an auxiliary material, and only a small amount of it is added to achieve a good technical effect;
[0154] 5. It can be seen from Examples 1-3 and Comparative Examples 11-12 that when preparing wood-stone materials, the order of adding the components will affect the wear resistance and mechanical properties of the wood-stone material products. Therefore, during preparation, the timing of adding the components needs to be strictly controlled.
[0155] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0156] 1. The present invention adds a carbon fiber / polyetheretherketone / polyethyleneimine composite to the wood-stone material system. The prepared wood-stone material has excellent wear resistance and mechanical properties. The carbon fiber has the characteristics of high temperature resistance, friction resistance, thermal conductivity and corrosion resistance. The polyetheretherketone has excellent characteristics such as high strength, high stability and easy processing. After being combined with the carbon fiber, it can also improve the poor compatibility of the carbon fiber in the system. The addition of a small amount of polyethyleneimine can further enhance the connection strength between the carbon fiber and the polyetheretherketone on the one hand, and further improve the compatibility of the composite in the system on the other hand;
[0157] 2. The present invention performs pre-treatment modification on carbon fiber, which is beneficial to improving the compatibility of polyetheretherketone, polyethyleneimine and carbon fiber and the interlayer bonding strength, so that the prepared composite has excellent compatibility and mechanical properties;
[0158] 3. When the present invention pre-treats and modifies the carbon fiber, controlling the amount of polydopamine powder and carbon nanotube powder added is beneficial to further enhance the compatibility of the carbon fiber with polyetheretherketone and polyethyleneimine;
[0159] 4. The present invention strictly controls the addition ratio of the three components of carbon fiber, polyetheretherketone and polyethyleneimine to better improve the mechanical properties and wear resistance of the prepared carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0160] 5. In the material selection for preparing the composite, the present invention uses carbon fiber, polyetheretherketone and polyethyleneimine for compounding, and the three components have a synergistic effect. According to the experimental verification in the comparative example, replacing polyetheretherketone with polyethylene or only using carbon fiber composite polyetheretherketone or only using carbon fiber composite polyethyleneimine cannot achieve the technical effect of using the carbon fiber / polyetheretherketone / polyethyleneimine composite;
[0161] 6. When preparing the wood-stone material, the present invention strictly controls the order and timing of adding each component, so that the prepared wood-stone material has excellent wear resistance and mechanical properties;
[0162] 7. The preparation method of the present invention is simple, the process is easy to operate, and is suitable for industrial production.
[0163] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0164] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly wear-resistant self-reinforced wood-stone material, characterized in that: The invention comprises the following components in parts by weight: 100-120 parts of stone powder, 50-80 parts of wood powder, 15-30 parts of polyvinyl chloride, 10-20 parts of aluminum hydroxide, 10-15 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2-2.5 parts of foaming agent, 10-15 parts of foaming regulator, 5-7 parts of stabilizer, 0.6-1.5 parts of stearic acid and 0.4-0.6 parts of oxidized polyethylene wax; The preparation method of the carbon fiber / polyetheretherketone / polyethyleneimine composite is as follows: 1) Weigh carbon fiber, polyetheretherketone, and polyethyleneimine for later use; 2) Add polyetheretherketone and polyethyleneimine into a 330-350°C water bath and heat for 15-25 minutes. When polyetheretherketone and polyethyleneimine are melted and flowed, add plasticizer and defoamer and stir them thoroughly. 3) adding carbon fiber to the system of step 2) and further stirring evenly; 4) Add the curing agent to a 60-80°C water bath and heat for 15-25 minutes. When it is molten and flowing, add it to the system of step 3), accelerate the stirring until the composite material is evenly mixed, perform compression molding, and place it at room temperature to gradually cool and solidify; The carbon fiber is pre-treated before being put into preparation, and the pre-treatment method is as follows: 1) Place the carbon fiber in an extractor for reflux treatment to remove surface rubber and impurities; 2) Adding polydopamine and carbon nanotube powder into acetone, stirring the mixture continuously for 1 to 2 hours, and ultrasonically dispersing the mixture for 0.5 to 1 hour to make it uniformly dispersed; 3) Soak the carbon fiber in the suspension prepared in step 2) for 40 to 60 seconds, take it out, and dry it at 85 to 95° C. for 2 to 2.5 hours. The pretreatment is completed.
2. The highly wear-resistant self-reinforced wood-stone material according to claim 1, characterized in that: The mass ratio of the carbon fiber, the polyetheretherketone, and the polyethyleneimine is 1:(2.5-3.5):(0.2-0.4).
3. The highly wear-resistant self-reinforced wood-stone material according to claim 1, characterized in that: The added amounts of the plasticizer and the defoamer are 0.5-0.8% of the total amount of the polyetheretherketone and the polyethyleneimine respectively.
4. The highly wear-resistant self-reinforced wood-stone material according to claim 1, characterized in that: The curing agent is polyamide; the plasticizer is dibutyl phthalate; and the defoaming agent is dimethyl silicone oil.
5. The highly wear-resistant self-reinforced wood-stone material according to claim 1, characterized in that: The added amount of the polydopamine powder is 1-1.5% of the mass of the acetone, and the added amount of the carbon nanotube powder is 0.4-0.8% of the mass of the acetone.
6. The highly wear-resistant self-reinforced wood-stone material according to claim 1, characterized in that: The foaming agent is sodium lauryl sulfate or sodium fatty alcohol polyoxyethylene ether sulfate; the foaming regulator is any one of ZB-530, K-400 and JINHASS foaming regulators; and the stabilizer is an organic tin stabilizer or a calcium zinc stabilizer.
7. The method for preparing the highly wear-resistant self-reinforced wood-stone material according to any one of claims 1 to 6, characterized in that: The specific steps include: S1. Raw material preparation: weigh 100-120 parts of stone powder, 50-80 parts of wood powder, 15-30 parts of polyvinyl chloride, 10-20 parts of aluminum hydroxide, 10-15 parts of carbon fiber / polyetheretherketone / polyethyleneimine composite, 2-2.5 parts of foaming agent, 10-15 parts of foaming regulator, 5-7 parts of stabilizer, 0.6-1.5 parts of stearic acid and 0.4-0.6 parts of oxidized polyethylene wax; S2. Mixing and batching: The stone powder, wood powder, polyvinyl chloride, and aluminum hydroxide are first mixed evenly, and then the foaming agent and the foaming regulator are added and mixed again. After mixing evenly, the carbon fiber / polyetheretherketone / polyethyleneimine composite is added; S3 extrusion: the mixture is placed in an extruder, until the mixture is melted and blended uniformly, a stabilizer, stearic acid and polyethylene oxide are added, and blended uniformly, and the blend is extruded; S4. Molding and cooling: The extruded mixture is cooled and vacuum-shaped through a mold; S5. Cutting and trimming: Cut and trim the formed products according to production requirements; S6. Inspection: Carry out quality inspection on the products, check their size, appearance and performance, and produce and put them into storage after they pass the inspection.
8. Door panels or door frames made of the highly wear-resistant self-reinforced wood-stone material according to any one of claims 1 to 6 or the wood-stone material prepared by the method for preparing highly wear-resistant self-reinforced wood-stone material according to claim 7.
Citation Information
Patent Citations
Wear-resistant carbon fiber modified polyether-ether-ketone composite material and preparation method thereof
CN105566844A
High-strength power cable protective tube and preparation method thereof
CN107163360A
Composite pipe for sewerage system and preparation method of composite pipe
CN112812468A
Chemical-resistant and high-temperature-resistant basalt fiber composite material
CN115926418A